The international response of primary health care to COVID-19: document analysis in selected countries - Nilia Maria de Brito Lima Prado; Thais Regis Aranha Rossi; Sônia Cristina Lima Chaves; Sandra Garrido de Barros; Laio Magno; Hebert Luan Pereira Campos dos Santos; Adriano Maia dos Santos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
This study examines the primary health care (PHC) organization in response to the COVID-19 epidemic. This is a descriptive study based on the document analysis of the countries' responses to the coronavirus pandemic with emphasis on PHC. In various countries, there have been different organizations and impacts of strategies since they have conducted actions according to the local characteristics of disease transmission, demography, public health services organization, and health system's capacity and financing, especially in the PHC area. A significant change during the pandemic has been the increase in telephone and video consultations incorporating health information technology. An efficient PHC, guided by essential actions, achieves more suitable results. Also, each country's cumulative capacity or experience makes the difference facing the emerging demands on different health systems.